2015
DOI: 10.33064/ippd1626
|View full text |Cite
|
Sign up to set email alerts
|

Editorial

Abstract: espacio donde se discutan temas de vanguardia relacionados con este campo. Los artículos que conforman el presente número son, en su mayoría, trabajos de investigación y, en menor proporción, artículos de reflexión teórica, los cuales fueron presentados durante

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
5

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 0 publications
0
5
0
5
Order By: Relevance
“…In both cases it is observed that the scores tend to increase as the children progress through school, and that the increase is basically down to the girls, since the boys’ scores remain fairly stable. These results seem to indicate that girls’ behaviour tends to get worse when they start CSE, which may be due to the fact that gender expectations tend to become more flexible from nine years onwards, as indicated by Palacios and Hidalgo (1999), although the intensity of the change is not particularly large.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In both cases it is observed that the scores tend to increase as the children progress through school, and that the increase is basically down to the girls, since the boys’ scores remain fairly stable. These results seem to indicate that girls’ behaviour tends to get worse when they start CSE, which may be due to the fact that gender expectations tend to become more flexible from nine years onwards, as indicated by Palacios and Hidalgo (1999), although the intensity of the change is not particularly large.…”
Section: Discussionmentioning
confidence: 88%
“…In other words, this study aims to address the question of whether the differences in the social reputation of boys and girls are the same regardless of age. Although the research shows that differences are fairly stable, some aspects exist which could influence social reputation and which could be related to changes in the establishment of gender roles depending on the child’s stage of development, as already indicated (Palacios & Hidalgo, 1999; Shaffer, 2002).…”
mentioning
confidence: 76%
See 3 more Smart Citations